Development of a digital pocket book on food and digestive system based on medicinal plants for lengkauk disease - Desti Rahmadani; Ruqiah Ganda Putri Panjaitan; Hayatul Fajri; Ary Kusmawati; Galih Albarra Shidiq (Universitas Muhammadiyah Malang, 2025)
The rapid development of digital-based learning highlights the need for innovative media that supports students’ understanding. At the same time, learning tools grounded in local wisdom remain scarce, especially those linking medicinal plant knowledge with food and digestive system content. The objective of this study is to assess the feasibility of a digital pocket book as a learning tool that focuses on food and the digestive system based on an inventory of medicinal plants for lengkauk disease. This research and development include potential and problems identification, data collection, product design, design validation, and design revision. The digital pocket book’s feasibility was assessed through validity testing by five validators using a validation sheet. The validated aspects included format, content, and language. The validation data were analyzed using Content Validity Ratio (CVR) and Content Validity Index (CVI). The digital pocket book validation results for food and digestive system material obtained a CVR value of 1.00 for each criterion in each aspect, with a valid category, and a CVI value of 1.00 with a valid category. Therefore, the digital pocket book developed in this study is suitable for use as a learning medium.